Konsep Keharmonisan Rumah Tangga dalam Al-Quran ( Interpretasi Ma’na-Cum-Maghza atas Term Libas dalam QS. Al-Baqarah: 187 ) - Sari, Maula; Fahrudin, Fahrudin (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2021)
AbstractThis research focuses on the study of